The unforeseen orbital tumor - Singh, Srishti; Raghavan, Bagyam; Geethapriya, Sivaramalingam; Govindaraj, Jayaraj; Padmanabhan, G; Krishna, Murali; Arafath, Rasheed; Sathyasree, V V (Indian Journal of Radiology and Imaging, 2020)
Inflammatory myofibroblastic tumor is a rare group of neoplasms showing a mixture of spindle-shaped myofibroblasts or fibroblasts and a variable amount of inflammatory cells (eosinophils, plasma cells, and lymphocytes). They are not usually included in the differential diagnosis of nodules and masses because of their rarity, therefore, remaining an underdiagnosed entity. We report one such rare case in a 3-year-old female.
Keywords: Inflammatory myofibroblastic tumor; myofibroblasts; rarity; underdiagnosed